Female Empowerment and Intimate Partner Violence - Elisabetta Calabresi; Núria Rodríguez-Planas (Institute of Labor Economics (IZA), 2025)
The chapter reviews the economic literature on intimate partner violence (IPV), a widespread human rights violation affecting nearly one in three women globally and generating significant societal costs. It focuses on the relationship between various dimensions of female empowerment and IPV. The chapter begins by outlining key theoretical frameworks—including household bargaining, instrumental violence, male backlash, and exposure theories—as well as the main data sources used to study IPV. It then reviews empirical evidence on how factors shaping female empowerment at the individual, relationship, community, and societal levels influence IPV outcomes. Central themes include labor market dynamics, education, income shocks, family formation, legal frameworks, institutional access, and gender norms. The chapter also considers how these factors interact across levels and discusses additional drivers of IPV not directly linked to female empowerment. The goal is to provide an overview of causal evidence from the economic literature on IPV while emphasizing its complexity and the importance of a context-specific, intersectional approach to both its analysis and prevention.
Keywords: J1; J12; 330; intimate partner violence